Synthesis of Activated Carbon/Chitosan/Alginate Beads Powder as an Adsorbent for Methylene Blue and Methyl Violet 2B Dyes - Margaretha Aditya Kurnia Purnaningtyas; Sri Sudiono; Dwi Siswanta (Universitas Gadjah Mada, 2020)
The activated carbon-chitosan-alginate (KKA) beads powder was synthesized to form an adsorbent for the cationic dyes, methylene blue (MB) and methyl violet 2B (MV 2B). The aims of this research were to determine the optimum composition of KKA beads powder for the adsorption of cationic dyes and to investigate the effect of pH, adsorbent mass, contact time, and initial concentration of MB and MV 2B dyes. A desorption study was also implemented to predict the adsorption mechanisms of MB and MV 2B dyes. The KKA beads powder was prepared by mixing chitosan, Na-alginate with various variation of masses (0.6; 0.8; 1.0; and 1.2 g) and activated carbon. The KKA beads were immersed in a CaCl2 solution. The KKA beads powder was characterized using FTIR spectroscopy and SEM. The desorption study was conducted in NaCl (0.1 M and 1.0 M), ethanol (40% and 60%), and pH 4 solution. The result showed that the KKA beads powder had been successfully created, with maximum adsorption capacities of 1.34 mmol g–1 for MB and 1.23 mmol g–1 for MV 2B. The kinetics and isotherms of MB and MV dyes adsorption on the KKA beads powder followed pseudo second order kinetics model and Freundlich isotherm. The desorption study showed that 60% ethanol was the most effective desorption solution for cationic dyes.